The Count of Monte Cristo [videorecording (DVD)] - Dumas, Alexandre, 1802-1870; Claflin, Sam, 1986-; Irons, Jeremy, 1948-; Girardot, Ana, 1988-; Følsgaard, Mikkel Boe (PBS, 2026)
Edmond Dantes, a young sailor, is falsely accused of treason and imprisoned in the Château d'If. After escaping and finding a hidden treasure, he reinvents himself as the wealthy and mysterious Count of Monte Cristo to exact revenge on those who betrayed him.